Modeling the role of fire and cooking in the competitive exclusion of Neanderthals. Issue 124 (November 2018) - Goldfield, Anna E.; Booton, Ross; Marston, John M.
Abstract: The Neanderthal body was more robust and energetically costly than the bodies of anatomically modern humans (AMH). Different metabolic budgets between competing populations of Neanderthals and AMH may have been a factor in the varied ranges of behavior and timelines for Neanderthal extinction that we see in the Paleolithic archaeological record. This paper uses an adaptation of the Lotka–Volterra model to determine whether metabolic differences alone could have accounted for Neanderthal extinction. In addition, we use a modeling approach to investigate Neanderthal fire use, evidence for which is much debated and is variable throughout different climatic phases of the Middle Paleolithic. The increased caloric yield from a cooked versus a raw diet may have played an important role in population competition between Neanderthals and AMH. We arrive at two key conclusions. First, given differences in metabolic budget between Neanderthals and AMH and their dependence on similar or overlapping food resources, Neanderthal extinction is likely inevitable over the long term. Second, the rate of Neanderthal extinction increases as the frequency of AMH fire use increases. Results highlight the importance of understanding the variable behaviors at play on a regional scale in order to understand global Neanderthal extinction. We also emphasize the importance of understanding the role of fire use in the Middle to Upper Paleolithic transition.